2015
DOI: 10.5056/jnm15111
|View full text |Cite
|
Sign up to set email alerts
|

The Low FODMAP Diet and Its Application in East and Southeast Asia

Abstract: There is growing interest in using food choice/dietary change to influence clinical outcomes in patients with irritable bowel syndrome (IBS). The low fermentable oligo-, di-, mono-saccharides, and polyols (FODMAPs) diet is an evidence-based approach that is gaining popularity in many Western countries. The low FODMAP diet is based on restricting dietary intake of short chain carbohydrates that are slowly absorbed or indigestible and not absorbed during passage through the small intestine. These are collectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 36 publications
2
60
0
1
Order By: Relevance
“…Recently, a published review article showed Korean dishes including kimchi and doenjang may have high fermentable oligo-, di-, and mono-saccharides; and polyols (FODMAP) ingredients. 31 We think that our study may be meaningful as a stepping stone to elicit the correlation between IBS symptoms and food, especially FODMAP. Interestingly, fiber intake was significantly higher in the group of participants with IBS than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a published review article showed Korean dishes including kimchi and doenjang may have high fermentable oligo-, di-, and mono-saccharides; and polyols (FODMAP) ingredients. 31 We think that our study may be meaningful as a stepping stone to elicit the correlation between IBS symptoms and food, especially FODMAP. Interestingly, fiber intake was significantly higher in the group of participants with IBS than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It proposes that specific nondigested or poorly digested carbohydrates contribute to common IBS symptoms and induce alterations in gut motility and secretion. 25 Low-FODMAP diets have been shown to reduce gastrointestinal symptoms if compared with both high-FODMAP diets 25 and National Institute for Health and Clinical Excellence standard dietary advice. 26 The efficacy of low-FODMAP diet has been questioned in a recent multi-center, parallel, single-blind RCT that showed no superiority of low-FODMAP diet compared to traditional dietary advice in improving IBS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…La dieta baja en mono, di, oligosacáridos y polioles fermentables (FODMAP) consiste en el consumo dietético reducido de carbohidratos de cadena corta, difíciles de digerir o poco absorbidos en el intestino delgado (51,52) Algunos estudios sugieren que esta dieta disminuye los síntomas funcionales intestinales y contribuye al mejoramiento del estatus nutricional en personas hospitalizadas con diarrea, y en el control de los síntomas en personas con SII (53,54). El estudio danés de Pedersen y colaboradores comparó el uso de esta dieta con probióticos y dieta occidental convencional, y demostró la utilidad de las primeras 2 medidas en el control sintomático del SII (16).…”
Section: Conflictos De Interésunclassified